The Influence of Transformational Leadership Style on The Work Motivation of Parepare City Health Service Employees With The Work Environment As a Mediation Variable - Tasrif Tasrif; Nur Asisah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
The Influence of Transformational Leadership Style On Employee Work Motivation With Work Environment As A Mediation Variable